Classical Gamelan Music Therapy for Sleep Quality and Cardiovascular Parameters in Third-Trimester Pregnant Women: A Case Series - Fitriana Kurniasari Solikhah; Hasanudin Hasanudin (Tarqabin Nusantara Group, 2026)
Background: Sleep disturbances severely impact third-trimester pregnant women, increasing adverseobstetric risks. Non-pharmacological interventions are strongly preferred, yet culturally congruenttherapies like classical gamelan music remain critically underexplored in clinical practice.Methods: In this prospective case series conducted between January and March 2026 in Indonesia, weenrolled three third-trimester pregnant women experiencing severe sleep disturbances (Pittsburgh SleepQuality Index [PSQI] >5). Participants received a 3-day classical gamelan music therapy regimen (10–15 minutes, twice daily). The primary outcomes included changes in PSQI global scores and sleepduration, as well as secondary cardiovascular parameters including blood pressure.Result: The three participants, aged 24 to 29 years, presented with severe baseline sleep fragmentation(mean PSQI 13.7). Following the intervention, individual PSQI scores decreased substantially (PatientA: 14 to 9; Patient B: 12 to 8; Patient C: 15 to 10). Mean nightly sleep duration increased from 3.8 to6.0 hours. Concurrently, resting heart rates decelerated from a mean of 102 bpm to 81 bpm, and systolicblood pressure normalized from 129 mmHg to 120 mmHg across all three individual participants.Conclusion: A brief regimen of classical gamelan music therapy appears feasible and is associated withmarked improvements in subjective sleep quality and autonomic regulation in third-trimester pregnantwomen. This culturally congruent, non-pharmacological intervention offers a safe, accessible adjunctivestrategy for gestational sleep management. Future large-scale randomised controlled trials withobjective polysomnographic endpoints are warranted to validate these preliminary findings and establishdefinitive clinical efficacy and safety.